Establishing Open Science Practices - Wilson, Micah; Schild, Christoph; Dunlop, Patrick (2019)
Open Science Practices (OSP) refer to a broad range of research practices, ultimately aimed at increasing the transparency, accessibility and reliability of scientific research. Open science is becoming increasingly important beyond intrinsic epistemological value; with many funding bodies, journals, and impact reporting requirements now expecting engagement with open science as standard. However, organisational psychology has not embraced OSPs to the same extent as other disciplines; providing opportunities for us to establish innovative solutions to our unique challenges, bottom-up.